Design Of Web-based Information System for Monitoring Class Lectures Case Study : STIKOM Surabaya - Hananto, Valentinus Roby; Sukmaaji, Anjik; Widodo, Arifin Puji (Jurnal JSIKA, 2012)
As one of the institutions in education, STIKOM Surabaya also had evaluation of learning outcomes that is Ujian Tengah Semester (UTS) and Ujian Akhir Semester (UAS). One of the purpose is to evaluate student learning outcomes of a course for one semester. For students, the results of UTS and the UAS is also one determinant of whether they graduated or not from the course they follow. For teachers, student test results can also be a reference for monitoring the level of student material understanding. From the results of evaluation classes, professors or teachers can monitor the success of the delivery of material in class. In addition, lecturers can also compare the results of his/her class with another parallel class. However, at present, there is no application or system that aims to compare the results of examinations per subject material between parallel classes. This application or system was built to analyze the results of class evaluations to determine the level of success topics material. The application also produces comparisons of evaluation results between parallel classes with the Kruskal-Wallis test. From the implementation and evaluation that has been done, the application can display the score comparison per topic material. By using the Kruskal-Wallis test, this application can display comparison information about mastery of the material between parallel classes. From the results of Kruskal-Wallis test we know whether there are significant differences in the mastery of the material between parallel classes, so the successful delivery of material between parallel classes as possible can be controlled. Keywords: information system, monitoring, evaluation, kruskal-wallis.